Aprendizados para o Brasil do desenvolvimento de pilhas a combustível de óxido sólido com base na experiência dos Estados Unidos e Japão: uma análise a partir de patentes e dos Sistemas Nacionais de Inovação - Marina Domingues Fernandes (2016)
The growing number of discussions about sustainable development highlight the difficulty of using renewable sources of energy on a global scale. Oxide-Solid Fuel Cells are one of the most efficient and promising technologies for sustainable power generation. These cells generate energy from hydrogen, obtained through both fossil fuels (such as natural gas) and renewable sources (such as bioethanol). Regardless of the fuel, the device generates energy with a higher efficiency. The present work proposes to discuss the technological path of the Solid Oxide Fuel Cells on the grounds of the concept of National Systems, complementing the analyses with sustainable development matters and historical facts intrinsic to the technology development itself. In order to do so, three countries guided this study, besides Brazil, the two others with most amount of published patents (around 70%), Japan and the US. The present work argumentation counts with a patent landscape including 5250 published patents from 1995 to 2015 and a panel company database comprising 66 SOFC related companies and research institutes. The present work presents the main characteristics of the Japanese and American National Systems of Innovation that favors the development of the cells, and the main contribution of this work is to identify the main learning of the development of such technology in Japan and the United States in order to suggest a model for a Brazilian production.